Challenges in Pancreatic Cancer - Dimitrova Kovacheva-Slavova, Mila; Georgiev Vladimirov, Borislav (IntechOpen, 2021)
Pancreatic cancer is one of the most lethal solid organ tumors with a poor five-year survival rate despite current oncological advances. The early and proper diagnosis of pancreatic cancer is of great importance for the improvement of the overall prognosis. This book provides an overview of the current challenges and states of pancreatic cancer and pancreatic neuroendocrine tumors, including information on diagnostic tools, treatment strategies, and mechanisms of pancreatic cancer therapy resistance.